Analisis Pembendungan Total Gerai Franchise Starbucks Coffee di Indonesia Menurut Hukum Bisnis - Patricia, Laura Sally; Lie, Gunardi (Peneliti.net, 2025)
This study focuses on examining the complete containment of Starbucks coffee franchise establishments in Indonesia, with Starbucks Coffee serving as the primary case study. A legal approach is employed to delve into the regulatory framework governing this issue, aiming to understand the fundamental principles impacting business actors and commercial competition. The objective of this research is to thoroughly explore the key aspects of regulating franchise establishment containment, while considering factors of economic sustainability and fairness to all parties involved. The anticipated outcome of this study is to provide a comprehensive understanding of the relevant regulations and their implications for business entities and market competition. Furthermore, it is envisaged that this research will contribute significantly to the formulation of policies that are not only effective but also equitable, aligning with the principles of economic sustainability. Ultimately, these endeavors aim to strike a delicate balance between imposed restrictions and the freedom to conduct business.